Hierarchical NiMo-based 3D electrocatalysts for highly-efficient hydrogen evolution in alkaline conditions. (September 2016) - Fang, Ming; Gao, Wei; Dong, Guofa; Xia, Zhaoming; Yip, SenPo; Qin, Yuanbin; Qu, Yongquan; Ho, Johnny C.
Abstract: In recent years, electro- or photoelectrochemical water splitting represents a promising route for renewable hydrogen generations but still requires the substantial development of efficient and cost-effective catalysts to further reduce the energy losses and material costs for scalable and practical applications. Here, we report the design and development of a hierarchical electrocatalyst constructed from microporous nickel foam and well-assembled bimetallic nickel-molybdenum (NiMo) nanowires, which are capable to deliver current densities as comparable to those of the state-of-the-art Pt/C catalyst at low overpotentials and even larger current densities at higher overpotentials (>124 mV). This binder-free 3D hydrogen evolution cathode catalyst also exhibits the excellent stability, without any decay of the current density observed after long-term stability tests at a low current density of 10 mA cm −2 and a high current density of 50 mA cm −2 . By pairing this NiMo 3D cathode with a NiFe-based anode, a water electrolyzer can be achieved with a stable current density of 10 mA cm −2 for overall water splitting at a voltage of ~1.53 V, indicating that the water splitting can be indeed realized without any performance sacrifice by using earth abundant electrocatalysts. Graphical abstract: A hierarchical electrocatalyst is constructed from microporous nickel foam and well-assembled bimetallic nickel-molybdenum (NiMo) nanowires, which is capable to catalyze hydrogen evolution with an activity comparable to that of state-of-the art precious Pt/C catalyst. Highlights: Nanostructured NiMo alloy can catalyse HER comparable to that does by Pt/C. This 3D catalyst also shows excellent stability over long-term tests. A current density of 10 mA cm -2 achieved for overall water splitting at 1.53 V.